The Significance of Michael Porter’s Theories in the Development of Smallholders Awareness Training Model (SAT-Model) - Marzukhi, Hassan; Murni Yunus, Mawar; Bibi Mustafa Hameed, Latiffa; Mohd Jamild, Mohd Ridwan (Jurnal Manajemen, 2026)
This paper explores the adaptation and integration of Michael Porter’s strategic-management theories—particularly the Five Forces Model, Value Chain Framework, and Generic Strategies of Competitive Advantage—in developing the Smallholders Awareness Training (SAT) Model. The SAT-Model was created to strengthen the competitiveness, ethical awareness, and sustainability of Malaysian oil-palm smallholders, aligning their activities with both Islamic Business Ethics (IBE) and Good Agricultural Practices (GAP). The study applied a Design and Development Research (DDR) approach consisting of three phases: need analysis, model design and development, and usability evaluation. The model synthesises Porter’s analytical logic with Islamic ethical and social values, establishing a framework for both competitive and moral excellence. Results show that Porter’s theories effectively guided the model’s competitiveness dimension, while IBE ensured that the pursuit of profit was balanced by divine accountability. This integration demonstrates how modern strategic frameworks can be localised for agricultural and ethical transformation in emerging economies.